Pengaruh Problem-Based Learning Berbantuan Video terhadap Keterampilan Berpikir Kritis dan Literasi Lingkungan Siswa dalam Pembelajaran Ekosistem - Anisa Pramesti; Widya Arwita (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
The low level of students' critical thinking skills and environmental literacy, as reflected in Indonesia's poor performance in PISA, along with the still-dominant use of conventional, teacher-centered learning methods, served as the background of this research. Which limit students' active participation and higher-order thinking development in ecosystem learning. This study aims to examine the effect of the Problem-Based Learning (PBL) model assisted by video media on students' critical thinking skills and environmental literacy in ecosystem learning. This study employed a quasi-experimental research design with a non-equivalent control group design. The research was conducted at SMAS Angkasa 1 Lanud Soewondo Medan, involving Grade X students in the even semester of the 2025/2026 academic year. Data were collected through pretest and post-test instruments measuring critical thinking skills and environmental literacy, which encompassed three components: knowledge, attitude, and behavior. The data analysis was performed using descriptive statistics and an independent sample t-test. The results indicate that students in the experimental class who were taught using the video-assisted PBL model demonstrated significantly higher critical thinking skills and environmental literacy scores compared to students in the control class who received conventional instruction. These findings contribute to the development of science, particularly by providing empirical evidence on the effectiveness of video-assisted PBL in enhancing critical thinking skills and environmental literacy, and by offering a reference for future research and innovation in biology education.